Automat cellule technique for Timetable problem - Ali. Alarabi , Khadija. Binyahmed (Journal of Pure & Applied Sciences, 2018)
In this paper we try engage to one of the famous educational problem. A timetable is a combinatorial optimization problem where there are allot of suggested solutions proposed for weekly table and authors for semester. This type of problem is a dynamic. The purpose from these solutions to escape from the clashes that exist frequently. here we going to present one technique with which we try to solve this problem. Our technique is an automat cellule. With this technique we will use a matrix to distribute the courses. Our matrix is a two dimension table. Probabilistic method to escape from clashes. This technique work with some roles which controls the cellule in the network.